2018
DOI: 10.1017/s2040174417001015
|View full text |Cite
|
Sign up to set email alerts
|

Formula derived Maillard reaction products in post-weaning intrauterine growth-restricted piglets induce developmental programming of hepatic oxidative stress independently of microRNA-21 and microRNA-155

Abstract: We recently reported augmentation of lipid peroxidation products in the liver of intrauterine growth-restricted (IUGR) piglets fed a high load of Maillard reaction products (MRPs) during suckling period. The underlying mechanisms of MRPs effects remain unknown. Here, we studied the long-term impact of MRPs exposure on liver oxidative status of IUGR juvenile pigs. Livers of 54-day-old pigs suckled with formula containing either a high (HHF, n=8) or a low (LHF: n=8) load of MRPs were analyzed for protein carbony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
(92 reference statements)
0
8
0
1
Order By: Relevance
“…Animal experiments have shown that chronic intake of dietary AGEs induces insulin resistance (Cai et al 2012), accelerates the progress of renal fibrosis (Feng et al 2007), liver inflammation (Patel et al 2012), might cause oxidative status impairment (Firmin et al 2018) and even loss of spatial memory in a model of neurodegeneration (Lubitz et al 2016). More importantly, an interventional study in humans has shown that a reduction of AGEs intake improves insulin sensitivity, indicating potential preventive/therapeutic efficiency (Uribarri et al 2011).…”
Section: Vol 68mentioning
confidence: 99%
“…Animal experiments have shown that chronic intake of dietary AGEs induces insulin resistance (Cai et al 2012), accelerates the progress of renal fibrosis (Feng et al 2007), liver inflammation (Patel et al 2012), might cause oxidative status impairment (Firmin et al 2018) and even loss of spatial memory in a model of neurodegeneration (Lubitz et al 2016). More importantly, an interventional study in humans has shown that a reduction of AGEs intake improves insulin sensitivity, indicating potential preventive/therapeutic efficiency (Uribarri et al 2011).…”
Section: Vol 68mentioning
confidence: 99%
“…4 High concentrations of reactive oxygen species (ROS) as well as oxidative injury reported in a growing number of studies suggest that IUGR leads to oxidative stress (OS) in the neonates. 5 Such phenomenon can be ascribed to the dysfunction of mitochondria and the impairment of the antioxidant defense system 6 both of which are related to restricted growth and development during gestation. 7 Neonates experiencing IUGR demonstrate oxidative injury within the intestine, 8 lung 9 and liver.…”
Section: Introductionmentioning
confidence: 99%
“…One such mechanism is miRs, which are small, non-coding RNA molecules that silence target genes through mRNA degradation or repressed protein translation. Numerous miRs have been demonstrated to have aberrant postnatal expression in growth-restricted offspring, leading to cellular stress that precedes impaired function of metabolic organs [ 51 , 86 , 87 , 88 ]. Recent studies found that the translation of p66Shc protein is directly inhibited by miR-203a-3p, leading to the attenuation of liver injury and fibrosis in mice [ 56 ].…”
Section: Discussionmentioning
confidence: 99%